LIPID PEROXIDATION MARKER LEVELS AND BASIC LABORATORY HEALTH INDICATORS OF BLOOD DONORS DURING WARTIME: POSSIBLE CONSEQUENCES FOR PRESERVED PACKED RED BLOOD CELLS QUALITY - Kalynychenko, Tetiana; Anoshyna, Militina; Malygon, Olena; Belousov, Andriy; Yagovdik, Maryna; Parubets, Lidiia; Belousova, Kateryna (Eastern Ukrainian Medical Journal, 2024)
Introduction. During storage at a moderately low-temperature of 4–6 °C, a preserved packed red blood cells (PRBCs) undergo metabolic and morphological changes commonly known as "storage lesion" or in vitro aging. Such changes inevitably increase during the permitted storage period, which is usually 21-42 days. But the degree and speed of their development in each individual preserved PRBCs unit is largely related to the special donor characteristics. The initial level of pro-oxidant process activities in the donor's body at the blood donation time can be an important starting point for the further kinetics of pathological changes since oxidative reaction activations are considered one of the main pathophysiological erythrocyte aging pathways. In particular, intense peroxidation of lipids as the main structural components of cell membranes causes significant changes with a usually negative impact on the dynamics and quality of cell physiological processes, and the induction of apoptosis and necrosis.Numerous oxidative stress causes with adverse health consequences, such as acute and chronic psychological stress, significant physical exertion, work in adverse environmental conditions (air temperature, smog, altitude), etc., are known today. So, the danger of the spread of the conditions described above, which are frequent during the war period, both among the military and the civilian population, can significantly affect public health in Ukraine as a whole with an indirect negative impact on blood donation. Therefore, the activity levels of lipoperoxidation processes in the donor's body, along with other blood indicators that characterize the functional state of the main organs and systems, are critically important for the preservation of the blood components provided by this donor, in particular PRBCs.The work aimed to study individual laboratory indicators of the donors' health during wartime. A number of tasks to be performed were set, namely: to investigate the lipoperoxidation activity in venous blood, as well as the liver functional state, iron metabolism, indicators of a general blood analysis; to compare the data obtained in the studied group of wartime donors with the corresponding indicators obtained from archival data in the group of peacetime donors.Materials and Methods. General blood analysis, protein metabolism, liver functional state, iron metabolism, and venous blood lipid peroxidation activity level were studied in donors. The research group included wartime donors of the Kharkiv region (2023 donations), whose activity types were military, civilian, and critical infrastructure. Archival data on donations from the pre-war period 2007 (І) were considered a comparison group (ІІ). Statistical processing and data analysis were performed using STATISTICA 10 (StatSoft, USA). Since the distribution of the trait was not normal, the non-parametric Mann-Whitney U test was used to assess the differences between the two independent groups. Differences between the results were considered significant at p-value <0.05.Results. It was established that the pro-oxidant activity indicators in the wartime blood donors significantly exceeded the control group indicators. This was evidenced by the data on the content of the entire range of lipid peroxidation molecular products, where the data excess of the experimental group compared to the control group ranged from 1.7 to 17.7 times. Thus, the levels of substrates and molecular peroxidation products of lipids extracted to the heptane phase (neutral lipids) were, in accordіng to the groups and the investigated indicators: for substrates (isolated double bonds (IDB)) - Me (I) = 2.40 (2.07; 3.35) U/ml vs Me (II) = 0.47 (0.19; 1.41) U/ml, p = 0.000001; for intermediate products such as dienic (DC), trienic (TC) and oxodienic conjugates (ODC) - Me (I) = 1.84 (2.07; 2.78) U/ml vs Me (II) = 0.10 (0.29; 0.91) U/ml, p = 0.000001; Me (I) = 0.56 (0.46; 0.82) U/ml vs Me (II) = 0.16 (0.13; 0.26) U/ml, p = 0.000001; Me (I) = 0.55 (0.44; 0.82) U/ml vs Me (II) = 0.15 (0.11; 0.25) U/ml, p = 0.000001; and for the Schiff bases type end products (ShB) - Me (I) = 0.15 (0.10; 0.28) U/ml vs Me (II) = 0.02 (0.02; 0.04) U/ml, p = 0.000001. Phospholipid peroxidation products, determined in the lipid extract isopropanol phase, also had significant intergroup differences, namely: according to the IDB concentration - Me (I) = 4.39 (3.89; 4.87) U/ml vs Me (II) = 1.63 (1.21; 1.92) U/ml, p = 0.000001; for the DC, TC, and ODC concentrations, respectively, - Me (I) = 2.07 (1.72; 2.62) U/ml vs Me (II) = 0.91 (0.65; 1.09) U/ ml, p = 0.000001; Me (I) = 1.09 (0.91; 1.36) U/ml vs Me (II) = 0.65 (0.48; 0.77) U/ml, p = 0.000001; Me (I) = 1.05 (0.86; 1.45) U/ml vs Me (II) = 0.50 (0.42; 0.61) U/ml, p = 0.000001; and for the ShB concentration - Me (I) = 0.26 (0.14; 0.43) U/ml vs Me (II) = 0.13 (0.08; 0.16) U/ml, p = 0.000001. The data of the general blood analysis, protein metabolism, functional state of the liver, and iron metabolism were within the reference values.The significant role of oxidative stress in PRBC aging during cold storage, accompanied by a substantial deterioration of their transfusion efficiency, confirmed by many studies, confirms the importance of the demonstrated results and the continuation of work in the chosen direction.Conclusions. The revealed features of the pro-oxidant activity of blood donors can influence the stability of their erythrocytes to standard long-term storage conditions at a temperature of 4-6 °C. Further research in the direction of analyzing the relationships between oxidative stress markers, in particular the lipoperoxidation activity, as special parameters of the donor, as well as substantiating the feasibility of considering these and other additional donor factors of the rate of erythrocyte aging development during storage are promising from the point of view of finding ways to improve the blood component quality.